Effects of financial development, FDI and good governance on environmental degradation in the Arab nation: Dose technological innovation matters? - Ju, Shuwen; Andriamahery, Anselme; Qamruzzaman, Md; Kor, Sylvia (Frontiers in Environmental Science, 2023)
The motivation of the study is to gauge the impact of financial development, FDI, technological innovation, and good governance on environmental degradation in the Arab Nation for the period 1991–2019. Several techniques have been implemented, including error correction-based cointegration, cross-sectional ARDL, nonlinear ARDL, and the heterogeneous causality test for directional causality. The slope of homogeneity, CSD, and unit root test results obtained with CIPS and CADF revealed that research variables have heterogeneity properties, are cross-sectionally dependent, and all variables become stationary after the first difference. An error-correction-based cointegrating test establishes the cointegration between explained and explanatory variables. Referring to the results from CS-ARDL, the study exposed that financial development has a detrimental effect on environmental sustainability, suggesting the intensification of CO2 emissions and ecological instability. On the other hand, the role of FDI, GG, and TI exposed beneficiaries to mitigating environmental adversity. The asymmetric assessment showed an asymmetric relationship between the explained and core explanatory variables. This relationship holds in both the long-term and the short-term. Finally, the casual association revealed bidirectional causality between FDI, TI, and ED [FDIED; TIED]. On the policy side, the study called for efficient monitoring of environmental improvement through financial channels in the case of credit extension and integration with existing environmental policies.